2021
DOI: 10.22461/jhea.1.71626
|View full text |Cite
|
Sign up to set email alerts
|

Counterfeit/Fake and Substandard Medicines – A Global Bioethical Issue Requiring A Global Approach

Abstract: Counterfeit drugs are a global problem and a public health hazard. Nearly 10 percent of all medicines sold worldwide are fake, leading to an estimated 100,000 deaths each year, equating to an additional economic burden of close to $200 billion annually. Counterfeit medicines also thwart public health efforts to control infectious diseases like Covid-19 and Tuberculosis and lead to the worsening of other public health crises such as anti-microbial resistance (AMR). According to the CDC, more than 2.8 million an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Medicine recalls have been reported all around the world including the West [2][3][4][5][6][7][8][9][10][11][12][13][14][18][19][20][21][22][23][24]. However, review articles have shown that this is a signi cant problem in developing countries, and most cases reported were from Asia and Africa compared to European and American continents [4,11].…”
Section: Introductionmentioning
confidence: 99%
“…Medicine recalls have been reported all around the world including the West [2][3][4][5][6][7][8][9][10][11][12][13][14][18][19][20][21][22][23][24]. However, review articles have shown that this is a signi cant problem in developing countries, and most cases reported were from Asia and Africa compared to European and American continents [4,11].…”
Section: Introductionmentioning
confidence: 99%
“…Medicine recalls have been reported all around the world including the West [2][3][4][5][6][7][8][9][10][11][12][13][14][18][19][20][21][22][23][24]. However, review articles have shown that this is a signi cant problem in developing countries, and most cases reported were from Asia and Africa compared to European and American continents [4,11].…”
Section: Introductionmentioning
confidence: 99%